2017
DOI: 10.1080/09593985.2017.1318988
|View full text |Cite
|
Sign up to set email alerts
|

Does kinesiophobia affect the early functional outcomes following total knee arthroplasty?

Abstract: The purpose of this study was to investigate the effects of kinesiophobia on early functional outcomes in patients following total knee arthroplasty (TKA) and how kinesiophobia is related to functional outcomes and pain. The Tampa Scale for Kinesiophobia (TSK), 2-minute walk test (2-MWT), and the timed up and go test (TUG) were used to assess 46 TKA patients on discharge day. The pain levels and active knee flexion range of motion (ROM) were recorded. Patients were divided into two groups as high kinesiophobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
3
38
0
2
Order By: Relevance
“…Findings of this study add body to the current evidence that demonstrates that kinesiophobia, among other psychological factors, can delay or hinder functional recovery in patients who have undergone orthopedic surgery [6,8,9]. Especially since 60% of the increase in pain score could be related to the presence of kinesiophobia [21].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Findings of this study add body to the current evidence that demonstrates that kinesiophobia, among other psychological factors, can delay or hinder functional recovery in patients who have undergone orthopedic surgery [6,8,9]. Especially since 60% of the increase in pain score could be related to the presence of kinesiophobia [21].…”
Section: Discussionsupporting
confidence: 61%
“…Kinesiophobia or fear of movement (FOM) is a well-known psychological factor that can influence patient outcome and recovery after trauma or surgery at the knee [6][7][8]. Patients with FOM are more likely to be physically inactive and depressed [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present result of lower extremity pain and avoidance of physical activity in patients with RA can be explained by the fear avoidance. According to this model fear may lead to the avoidance of functional behaviors such as walking which results in disability (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Kinesiophobia is defined as the fear and refusal of movement [ 17 ], based on the fear-avoidance model introduced by Vlaeyen et al [ 18 ]. In patients undergoing knee replacement, authors showed a negative correlation between high levels of kinesiophobia and reduced knee flexion [ 19 , 20 ], ambulatory performance [ 21 , 22 ], pain [ 20 , 22 ] and length of hospital stay [ 23 ]. In literature, Kinesiophobia was measured using the Tampa Scale and patients with high levels of Kinesiophobia were identified for scores greater than 40 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%